2010
DOI: 10.1176/appi.ajp.2010.09091259
|View full text |Cite
|
Sign up to set email alerts
|

Basal Ganglia Surface Morphology and the Effects of Stimulant Medications in Youth With Attention Deficit Hyperactivity Disorder

Abstract: Objective Disturbances in the basal ganglia portions of Cortico-Striato-Thalamo-Cortical (CSTC) circuits likely contribute to the symptoms of Attention-Deficit/Hyperactivity Disorder (ADHD). This study examines the morphologic features of the basal ganglia nuclei (caudate, putamen, and globus pallidus) in children with ADHD. Design We examined 104 individuals (47 with combined-type ADHD and 57 controls) aged 7 to 18 years, in a cross-sectional case-control study using anatomical magnetic resonance imaging. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 87 publications
8
70
4
Order By: Relevance
“…The effects of methylphenidate on striatal morphology echo clinical observations of medication-induced normalization of inward caudate nuclei deformations (Sobel et al, 2010). These findings are in line with a recent meta-analysis (Nakao et al, 2011) that indicated that in ADHD, and in terms of medication effects, the most prominent and replicable structural abnormalities occur in the basal ganglia.…”
Section: Methylphenidate Affects Striatal Morphology and Frontal Connsupporting
confidence: 83%
See 1 more Smart Citation
“…The effects of methylphenidate on striatal morphology echo clinical observations of medication-induced normalization of inward caudate nuclei deformations (Sobel et al, 2010). These findings are in line with a recent meta-analysis (Nakao et al, 2011) that indicated that in ADHD, and in terms of medication effects, the most prominent and replicable structural abnormalities occur in the basal ganglia.…”
Section: Methylphenidate Affects Striatal Morphology and Frontal Connsupporting
confidence: 83%
“…Similarly, childhood psychostimulant medication was found to normalize ADHD-related reductions of anterior cingulate cortex volume, whereas caudate nuclei volumes remained markedly reduced regardless of medication history (Semrud-Clikeman et al, 2006). Yet, the shapes of the caudate nuclei of untreated patients showed inward deformations that appeared normalized after psychostimulant treatment (Sobel et al, 2010). Longitudinal measurements of cerebral cortex thickness indicated that ADHD-associated excess cortical thinning during adolescence could be moderated by psychostimulant treatment (Shaw et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Among medication-naïve participants, there were volume reductions in putamen that were primarily driven by inward deformations of structures, including those nuclei within the putamen that are components of limbic, sensorimotor, and associative pathways. In contrast, those treated with stimulants had outward deviations of putamen nuclei, suggesting that stimulants may affect, and perhaps facilitate, development of basal ganglia morphology in ADHD (Sobel et al 2010) in a manner that serves to ameliorate ADHD-related deficits in executive and motor control. Admittedly, comparison of treated versus nontreated children with ADHD is complicated, in part because it is possible that groups may have differed in some systematic way before onset of treatment.…”
Section: Treatment With Stimulant Medication and Volumetrymentioning
confidence: 99%
“…A 5-year longitudinal study found smaller total white matter volume in unmedicated compared with medicated ADHD children (Castellanos et al 2002). More normative volumes in several brain areas, i.e., the inferior frontal cortex (Shaw et al 2009), cerebellum (Bledsoe et al 2009), basal ganglia (Sobel et al 2010), and anterior cingulate cortex have been found in chronically treated compared with unmedicated children. Pliszka et al (2006) reported more pronounced differences in the anterior cingulate cortex and ventrolateral prefrontal cortex during an inhibition task in drug-naïve ADHD compared with healthy children, but direct comparisons between drug-naïve subjects and subjects with a history of psychostimulant treatment revealed no differences.…”
Section: Introductionmentioning
confidence: 99%